The impact of disruptive innovation on the demand for coworking space - Bronkhorst, Johan (Department of Construction Economics and Management, 2021)
This thesis investigates whether the phenomenon of companies that seek to disrupt markets through innovation play a role in the rise of coworking spaces. The city of Cape Town in South Africa was selected as the location for this study due to an increase in the establishment of coworking spaces and the appearance of the aforementioned phenomenon. The premise for this thesis is based on the demands for commercial real estate, which has changed as a result of the implementation of new technologies and the sharing economy. This change is argued to have altered the way companies utilise working environments which, in turn, amended the requirements of these companies. The study seeks to establish whether coworking spaces serve as adequate supply to these demands or whether the increase in the establishment of coworking spaces is unaffiliated. Grounded theory was used as the research method in this study. Semi-structured interviews were conducted with seven respondents that were all active founders of coworking spaces at the time of the study. Additional documentary evidence was collected in cases where it was available. An analysis of the responses indicates that there is a strong relationship correlation between the rise of disruptive innovation and the increase in available coworking spaces. This relationship correlation was based on the value that flexibility, affordability and community facilitation held for companies that associate with disruptive innovation. These companies were mainly start-ups, skunkworks teams, research and development departments and other forms of companies that primarily work within the industry of technology. Limitations to the study included that additional documentary evidence was limited due to poor record-keeping of active memberships by coworking space operators, in addition to restrictions that were placed on accessing company information such as revenue statements. The research findings provide academic support and market-related evidence to developers and investors within the real estate sector that could enable them to make more informed decisions relating to the supply of coworking spaces. Moreover, the findings shed light on the general views shared by the founders of the coworking spaces. These views should provide insight to those interested in the industry, and more specifically within the Cape Town region.